Comparison of histidine-tryptophan-ketoglutarate (HTK) solution versus University of Wisconsin (UW) solution for organ preservation in human liver transplantation - Erhard, Jochen; Lange, R.; Scherer, R.; Kox, Wolfgang; Bretschneider, Hans Jürgen; Gebhard, Martha-Maria; Eigler, F. W. (Transplant international, 1994)
Over a 30-month period, 60 patients (30 in each group) suffering from end-stage liver disease or primary hepatic malignancy and scheduled for liver transplantation were enrolled in a prospective, randomized study to compare two methods of liver preservation: histidinetryptophan-ketoglutarate (HTK) solution versus University of Wisconsin (UW) solution. Entry criteria for both groups were: age (18-65 years), elective surgery (transplantable or urgent category of the recipients), first transplantations and harvesting procedure performed by the same team. The parameters under investigation were the clinical and laboratory data preand post-transplantation, as well as follow-up data such as complications and survival. There were no significant differences in the two groups as far as the evaluation criteria were concerned, even when cold ischemia time was more than 15h (n=7). A slight, yet not significant, increase in late complications of the biliary anastomoses could be seen in the UW group. Hepatocellular injury (SGOT, SGPT, GLDH, lactate) appeared to be more marked in the HTK group. These results suggest that both HTK and UW solutions are appropriate for clinical use in liver transplantation, even if cold ischemia time is more than 15h.
Gesehen am 12.03.2025